2017
DOI: 10.1186/s12906-017-1953-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of free radical scavenging and anti-proliferative activities of Tinospora cordifolia Miers (Willd)

Abstract: Background Tinospora cordifolia (Guduchi or Amrita) is an important drug of Ayurvedic System of Medicine and found mention in various classical texts for the treatment of diseases such as jaundice, fever, diabetes, cancer and skin disease etc. In view of its traditional claims, antioxidant and anti-proliferative activities were evaluated in the present study.MethodsEthanol extract (TCE) and subsequent petroleum ether (TCP), dichloromethane (TCD), n-Butanol (TCB) and aqueous (TCA) fractions of were prepared fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…The antioxidant activity analyzed by ABTS method in different extracts were ranging from 119.61 to 172.77 µmTE/g, wherein the highest activity was found in the ethyl alcohol and the least in the water extract. A similar study by Polu et al ( 2017 ), reported antioxidant activity by ABTS method in T. cordifolia which was between 28.24 and 132.4 IC 50 µg/mL, with exception of petroleum ether extract with more than 1000 IC 50 µg/mL. The results for the FRAP method of antioxidant activity in different extracts were found to be between 0.78 and 1.15 mmol Fe(II)/g, wherein ethyl alcohol and methanol depicted the highest content in comparison to acetone and water extracts.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The antioxidant activity analyzed by ABTS method in different extracts were ranging from 119.61 to 172.77 µmTE/g, wherein the highest activity was found in the ethyl alcohol and the least in the water extract. A similar study by Polu et al ( 2017 ), reported antioxidant activity by ABTS method in T. cordifolia which was between 28.24 and 132.4 IC 50 µg/mL, with exception of petroleum ether extract with more than 1000 IC 50 µg/mL. The results for the FRAP method of antioxidant activity in different extracts were found to be between 0.78 and 1.15 mmol Fe(II)/g, wherein ethyl alcohol and methanol depicted the highest content in comparison to acetone and water extracts.…”
Section: Resultssupporting
confidence: 62%
“…Whereas when compared among solvents, ethyl alcohol and methanol had a higher content of TFC compared with acetone and water (Table 1 ). Hydro-alcoholic extract of T. cordifolia plant was reported for TFC with 18.91 mg QE/g, whereas TFC of T. cordifolia stem extracts in ethyl alcohol, petroleum ether, dichloromethane, n -butanol, and aqueous solvents were reported between 0.17 and 0.98 mg QE/g (Polu et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanolic extract of Albizia procera showed strong scavenging activity against free radical compared to various standards 58 . These in-vitro assays indicate that this plant extract is a better source of natural antioxidant, which might be helpful in preventing the progress of various oxidative stresses [59][60][61][62] .…”
Section: In-vitro Free Radical Scavenging Activitymentioning
confidence: 79%
“…DPPH ï is a stable free radical resulting from the delocalization of the spare electron over the molecule. When DPPH ï is mixed with a substance donor of the hydrogen atom, its reduced form is produced (DPPH-H), in which it loses the violet color and forms a yellow color (17,18). On the other hand, the ABTS ï+ assay involves the direct production of the blue-green ABTS ï+ through the reaction between ABTS ï+ and potassium persulfate.…”
Section: Discussionmentioning
confidence: 99%